2013
DOI: 10.1182/blood-2013-01-481135
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of young and aged murine hematopoietic stem cells revealed by quantitative clonal analysis using cellular barcoding

Abstract: Key Points Quantitative clonal analysis demonstrates directional changes in contributions of stem cells to blood. The pool of aged hematopoietic stem cells is comprised of many, but small clones, while young stem cells are less numerous, but more potent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 28 publications
7
101
1
Order By: Relevance
“…For example, a previous analysis of a similarly configured barcode identified 30–50 barcodes per transplanted mouse, which was sufficient to provide insights into hematopoietic differentiation (35). Other gene marking studies utilizing different barcode designs have detected fewer than 100 different barcodes in different lineages of transplanted mice (31,32). The reliability of such analyses could be further enhanced if fully characterized barcode libraries of moderate complexity, such as that in the present study, are used to validate data analysis strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous analysis of a similarly configured barcode identified 30–50 barcodes per transplanted mouse, which was sufficient to provide insights into hematopoietic differentiation (35). Other gene marking studies utilizing different barcode designs have detected fewer than 100 different barcodes in different lineages of transplanted mice (31,32). The reliability of such analyses could be further enhanced if fully characterized barcode libraries of moderate complexity, such as that in the present study, are used to validate data analysis strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, paradigm-shifting research on HSC clonality and the heterogeneous contribution of HSC clones to hematopoiesis has recently challenged this view. Higher levels of clonality, where only a few clones actively contribute to the production of peripheral blood cells, has been observed with hematopoietic aging [61-63]. Historically, an aging-related progression towards hematopoietic clonality is demonstrated by skewing towards individual X-chromosome inactivation associated with myeloid bias in aged female individuals [64, 65].…”
Section: Hsc Clonal Contribution To Hematopoietic Agingmentioning
confidence: 99%
“…They further imply, based on sophisticated mathematical models, that the aging-associated myeloid bias might be a consequence of reduced multipotent progenitor (MPP) flux to common lymphoid progenitors (CLP) rather than a change in the HSC pool composition [63]. Verovskaya et al, using cellular barcoding and high-throughput sequencing to monitor clonal contribution to regenerative hematopoiesis, concluded that young mice present fewer active HSC clones producing high numbers of progeny, while in aged mice more active HSC clones are observed, but which produce fewer progeny [61]. These findings appear contradictory, but one explanation might be that clonality in steady-state hematopoiesis might differ from clonality in a regenerative setting such as BM transplantation.…”
Section: Hsc Clonal Contribution To Hematopoietic Agingmentioning
confidence: 99%
“…Unlike the extensive polyclonal repopulation seen in primates, murine studies demonstrated the behaviors of a single or a few repopulating clones per mouse(Copley et al, 2012; Jordan and Lemischka, 1990; Lemischka et al, 1986; Muller-Sieburg et al, 2012; Smith et al, 1991). Some recent studies have investigated oligoclonal repopulation (dozens of clones) in mice (Cornils et al, 2012; Gerrits et al, 2010; Lu et al, 2011; Naik et al, 2013; Verovskaya et al, 2013), nevertheless, translating these studies into understanding human repopulation is limited because of the far greater complexity of polyclonal reconstitution as well as the greater demands placed on stem cells within the larger and longer-lived human system. Thus, despite the significant advances in our understanding of the HSC biology from murine models, the functional properties of primate HSPCs following transplant remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%